Political Trust as a Predictor of Vote Buying Attitudes among New Voters - Nadipa, Salma Putri; Afifah, Sarah (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Vote buying activities that often occur close to general election contestations can influence the views of novice voters on politics in Indonesia, one of which is political beliefs. Therefore, this research aims to determine the relationship between political trust and vote buying attitude which was carried out using a correlational quantitative approach. The subjects used in the research were 347 novice voters in Palembang City who were obtained using a purposive sampling technique. The data was measured using the Political Trust Scale from Akhrani (2016), the Vote Buying Scale from Sumantri (2021). Data analysis in this research uses Pearson Product Moment correlation. The results of this study show that there is no relationship between political trust and vote buying attitude (r=-0.009, n=347, p=0.868). This means that there is no significant relationship between the two variables studied. Future research is expected to examine other variables that can influence political trust.Kegiatan vote buying yang sering terjadi mendekati kontestasi pemilihan umum dapat mempengaruhi pandangan pemilih pemula terhadap perpolitikan di Indonesia salahsatunya terhadap kepercayaan politik. Oleh karena itu, penelitian ini bertujuan untuk mengetahui hubungan political trust dan vote buying attitude yang dilakukan menggunkan pendekatan kuantitatif korelasional. Subyek dalam penelitian yang digunakan adalah 347 pemilih pemula di Kota Palembang yang diperoleh dengan teknik purposive sampling. Data yang diukur menggunakan Skala Polotical Trust dari Akhrani (2016), Skala Vote Buying dari Sumantri (2021). Analisis data dalam penelitian ini menggunakan korelasi Pearson Product Moment. Hasil penelitian ini menunjukan tidak adanya hubungan antara political trust dengan vote buying attitude (r=-0,009, n=347, p=0.868). Hal ini bermakna bahwa tidak adanya hubungan yang signifikan antara kedua variabel yang diteliti. Penelitian selanjutnya diharapkan untuk meneliti variabel lain yang dapat mempengaruhi political trust.